Application of Classical Music Therapy to Reduce Signs and Symptoms of Auditory Hallucinations - Wulandari, Retno Dwi; Widagdo, Agus; Purwaningsih, Iswanti (Global Health Science Group, 2024)
Hallucinations are a type of mental disorder where a person is unable to differentiate between real life and fake life. There are around 24 million schizophrenia patients in the world, while in DIY the incidence of mental disorders reaches 14,514 people. One effective non-pharmacological treatment for treating hallucinations is classical music therapy. Objective to understand the application of classical music therapy to reduce signs and symptoms of auditory hallucinations in schizophrenia patients. In this case study, 1 respondent was taken using the case study method with inclusion criteria, the instruments used were the classical music therapy SOP, the AHRS (Auditory Hallucination Rating Scale) assessment sheet and the assessment sheet for signs and symptoms of hallucinations. The application of Classical Music Therapy was carried out on 1 respondent, namely Mr.S. Before therapy, the patient's AHRS score was 18 and 9 on the score for observing signs and symptoms of hallucinations. After 5 days of therapy, the AHRS score was 8 and a score of 4 for observing signs and symptoms of hallucinations. Classical music therapy is effective in reducing the level of hallucinations and reducing signs and symptoms of auditory hallucinations in schizophrenia patients.